Evaluasi Penerapan PP No 71/2010 Tentang Standar Akuntansi Pemrintahan Berbasis Akrual: Studi Kasus di Pemda Nganjuk - Firdaus, Dahlia; Sayogo, Djoko Sigit; Latifah, Sri Wahjuni (Universitas Muhammadiyah Yogyakarta, Indonesia, 2015)
The purpose of this research was to determine the suitability of the accrual basis implementation on Governmental Accounting Standards in Peraturan Pemerintah (PP) No. 71/2010 at Nganjuk Regency’s Financial Statements year 2013. This research related with Dinas Pendapatan, Pengelolaan Keuangan dan Aset Daerah (Department of Revenue, Finance and Asset Management). Research proves that Nganjuk Regency’s Financial Statements not yet fully implementing the PP 71/2010. Nganjuk Regency’s financial statements still apply Enclosure II of PP 71/2010 that is cash toward accrual basis. This is due to the application of PP 71/2010 accrual basis (Enclosure I of PP 71/010) are required to be implemented in fiscal year 2015.